Composite shading container and preparation method thereof

The composite light-shielding container prepared by the three-layer co-extrusion method uses titanium dioxide, silica and mica powder of specific particle size to solve the problem of poor light-shielding effect of dairy packaging materials, thereby reducing costs and extending shelf life.

CN120663613APending Publication Date: 2025-09-19OTOR TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410305424.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-18
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Existing dairy product packaging materials have poor light-shielding effects, which causes light to penetrate and cause biochemical reactions. In addition, the production costs and equipment requirements are high, making it difficult to effectively extend the shelf life of dairy products.

Method used

A composite light-shielding container was prepared by a three-layer co-extrusion method. Titanium dioxide, silicon dioxide and mica powder of specific particle size were used, combined with a layered structure, to prepare a composite light-shielding container with excellent light-shielding performance.

Benefits of technology

Without affecting other properties, the production cost is reduced, the light-shielding ability is improved, the shelf life of dairy products is extended to about 20 days, and the blister processing is easy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120663613A_ABST
    Figure CN120663613A_ABST
Patent Text Reader

Abstract

The invention discloses a composite shading container which is prepared by adopting a three-layer co-extrusion method, comprises an outer layer, a middle layer and an inner layer, and comprises the following components in percentage by mass: 31-42% of carrier resin, 3-8% of titanium dioxide, 8-12% of silicon dioxide, 30-40% of mica powder, 3-7% of an opacifying agent, 0.5-2% of a dispersing agent and 0.1-0.4% of an antioxidant, the outer layer comprises 90-95% of carrier resin and 4-10% of white master batch, and the layer ratio accounts for 20%; the middle layer comprises 15-30% of carrier resin and 65-85% of light-blocking master batch, and the layer ratio accounts for 60%; the inner layer comprises 90-95% of carrier resin and 4-10% of white master batch, and the layer ratio is 20%. The invention further discloses a preparation method of the composite shading container. According to the composite shading container, the technical problems that an existing packaging container is high in production material cost and high in production equipment process requirement are solved. As a dairy product package, the shelf life can be prolonged to about 20 days, and the requirement of customers for prolonging the shelf life is further met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food packaging, and in particular relates to a composite light-shielding container for light-sensitive food and a preparation method thereof. Background Art

[0002] In dairy food packaging, in order to extend the shelf life of dairy foods, for some light-sensitive foods, high-barrier resins are generally used as specific materials to meet the requirements. Among commonly used packaging materials, barrier methods or light-proof methods are generally adopted. In blister packaging of dairy products, white barrier (mainly gas barrier) materials are often used. Barrier materials are generally PA or EVOH, and white mainly uses titanium dioxide or talcum powder as fillers; however, in order to achieve the state of light blocking and opacity under strong light, the proportion of titanium dioxide to be added is quite high, almost accounting for more than 70% of the overall mass fraction. This poses a serious challenge to the production of blister equipment and also brings huge cost pressure. The blister process requires that the packaging material is easy to extrude and stretch, but polypropylene materials with a titanium dioxide content of more than 70% are difficult to extrude and stretch into shape; at the same time, the high cost of production materials often makes it difficult for small and micro enterprises with low profits to survive.

[0003] In the dairy industry, the shelf life of fresh dairy products is often only a few days. For example, the shelf life of domestic fresh dairy products at 2-5°C after processing is 1-2 days. After multi-layer co-extrusion packaging, the shelf life of fresh dairy products can reach about 5-7 days. In order to further extend the shelf life, barrier materials are added, but the barrier material has a poor light shielding effect. Light passing through the packaging material can easily cause a series of biochemical reactions and cause dairy product spoilage. With the improvement of people's living standards and the increasing awareness of food conservation, we urgently need a packaging material that can further extend the shelf life of dairy products, especially in some industries that have high quality requirements for fresh dairy products and are sensitive to light. Therefore, it is necessary to further improve the shelf life of dairy products to meet the diverse needs of the market. Summary of the Invention

[0004] The present invention aims to address, at least to a certain extent, one of the technical problems in the related art. To this end, the present invention primarily aims to provide a composite light-shielding container, aiming to address the high material costs and demanding production equipment requirements of existing packaging containers for light-sensitive foods. The present invention also provides a method for preparing the composite light-shielding container.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A composite light-shielding container is prepared by a three-layer co-extrusion method, comprising an outer layer, a middle layer, and an inner layer, and comprising the following components by mass percentage: 31% to 42% carrier resin, 3% to 8% titanium dioxide, 8% to 12% silicon dioxide, 30% to 40% mica powder, 3% to 7% sunscreen, 0.5% to 2% dispersant, and 0.1% to 0.4% antioxidant;

[0007] The outer layer includes 90-95% carrier resin + 4-10% white masterbatch, and the layer ratio accounts for 20%; the middle layer includes 15-30% carrier resin + 65-85% light-blocking masterbatch, and the layer ratio accounts for 60%; the inner layer includes 90-95% carrier resin + 4-10% white masterbatch, and the layer ratio accounts for 20%.

[0008] In certain specific embodiments, the light-blocking masterbatch includes silicon dioxide, mica powder, a dispersant, a light-shielding agent, and an antioxidant.

[0009] In certain specific embodiments, the white masterbatch is one or more of titanium dioxide, calcium carbonate and polyethylene, and the sunscreen is polymethylsilsesquioxane with a particle size of 1-3 μm.

[0010] In certain specific embodiments, the titanium dioxide is rutile titanium dioxide, and the content of the titanium dioxide is ≥99%, the particle size is 0.15-0.25um, the tinting power is ≥100, and the oil absorption is 16≤%≤24.

[0011] In certain specific embodiments, the silicon dioxide is fumed silicon dioxide with a particle size of D50=8um-12um and an oil absorption of ≤75; the particle size of the mica powder is D50=8um-12um.

[0012] In certain specific embodiments, the dispersant is N,N'-ethylene bisstearamide; and the antioxidant is a hindered phenol antioxidant or a phosphite antioxidant.

[0013] A method for preparing the composite light-shielding container comprises the following steps:

[0014] 1) Masterbatch preparation: ingredients are prepared according to the formula requirements, mixed, melt-extruded, and the melt is pelletized, dried, and cooled to form a masterbatch. The temperature of the melt extrusion is controlled to be 10-40°C above the melting point of the carrier resin;

[0015] 2) Preparation of composite light-shielding container: The masterbatch prepared in step 1) is drawn into a sheet by multi-layer co-extrusion, and then calendered, preheated and blister-formed to obtain a composite light-shielding container.

[0016] In some specific embodiments, the process parameters of the melt extrusion in step 1) are a screw speed of 400-500 r / min, an extrusion pressure of 15-25 MPa, an extrusion temperature of 210-240°C, and an extrusion die temperature of 210-220°C.

[0017] In certain specific embodiments, the process parameters of the multi-layer co-extrusion in step 2) are: temperature 190-225° C., and pressure of the metering pump controlled at 7-12 MPa.

[0018] In some specific embodiments, the calendering process parameters in step 2) are: calendered sheet width 800 mm, thickness 3400 ± 50 μm, the three roller temperatures of the calendering rollers are respectively controlled at 30-35°C, 45-50°C, and 85-90°C, the cold roller temperature is controlled at 100°C, the sheet travel speed is 5-6 m / min, and the sheet temperature is controlled at 110-130°C.

[0019] In certain specific embodiments, the process parameters of the blister molding are: the temperature of the blister molding machine is 340-400° C., the air pressure is 6-8 MPa, and the time is 4-5 s.

[0020] Compared with the prior art, the present invention has at least the following advantages:

[0021] The composite light-shielding container provided by the present invention adopts titanium dioxide, silicon dioxide and mica powder of specific particle sizes, so that these substances form a complementary effect in particle size, and at the same time combine the layered structure of mica powder, supplemented by other carrier resins, dispersants and light-shielding agents, etc.; at the same time, combined with the specific layered structure, the prepared composite light-shielding container increases the light-blocking ability without affecting other product properties, reduces the production cost of the product, and is relatively easy to process and form by subsequent blister molding. After testing, the masterbatch is made into a sheet and the dairy product packaging after blister molding can extend the shelf life to about 20 days, further meeting the customer's requirements for extending the shelf life. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific embodiments of the present invention, the following briefly introduces the drawings required for the specific embodiments or the description of the prior art.

[0023] Figure 1 This is a diagram showing the light-shielding principle of TiO2 particles in the present invention. DETAILED DESCRIPTION

[0024] The present invention will be further described in detail below with reference to the accompanying drawings and examples. The following examples are merely illustrative and non-restrictive, and should not be used to limit the scope of protection of the present invention.

[0025] When expressing a certain amount, concentration or other value or parameter in the form of a range, preferred range, or preferred upper and lower numerical limits, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper range limits or preferred numerical values ​​with any lower range limit or preferred numerical value, without considering whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values ​​listed herein include the endpoints of the range and all integers and fractions within the range.

[0026] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.

[0027] The materials, methods, and examples herein are illustrative and, unless otherwise indicated, are not to be construed as limiting.

[0028] The composite light-shielding container provided in the present application is prepared by a three-layer co-extrusion method, including an outer layer, a middle layer and an inner layer, and includes the following components in mass percentage: 31% to 42% carrier resin, 3% to 8% titanium dioxide, 8% to 12% silicon dioxide, 30% to 40% mica powder, 3% to 7% sunscreen, 0.5% to 2% dispersant, and 0.1% to 0.4% antioxidant; and wherein the outer layer includes 90% to 95% carrier resin + 4% to 10% white masterbatch, and the layer ratio accounts for 20%; the middle layer includes 15% to 30% carrier resin + 65% to 85% light-blocking masterbatch, and the layer ratio accounts for 60%; the inner layer includes 90% to 95% carrier resin + 4% to 10% white masterbatch, and the layer ratio accounts for 20%.

[0029] The carrier resin is homopolypropylene (used for sheet or drawing, with a melt index of 2 to 4 g / 10 min) or copolymer polypropylene (used for injection molding, with a melt index of 20 to 30 g / 10 min);

[0030] The titanium dioxide is rutile-type titanium dioxide with a particle size of 0.15-0.25 μm, a tinting power of 500, and an oil absorption of 20. Titanium dioxide has high refractive index and high photostability. The main raw material of titanium dioxide is TiO2, whose crystals inherently have a refractive index of approximately 2.65-2.88. This refractive index is related to the particle size and the degree of dispersion of the particle structure: within a range greater than half the wavelength of visible light, the smaller the particle size, the smoother the particle structure, and the better the dispersion, the greater the hiding power. When the D50 of TiO2 is around 0.2 μm, its hiding power reaches its maximum. When light strikes TiO2, part of the light is refracted or scattered by the particles, preventing some light from passing through the sheet layer. When the human eye can see an object of a certain color, it is actually the visible light absorbed by the color or object that is reflected to the human eye. When the covering power reaches a certain level, it will completely block the visible light absorbed by the object or color, thus achieving the so-called light-blocking effect. There is also a diffraction phenomenon. When the TiO2 particles reach a certain size, diffraction will occur when the light hits the TiO2 particles. The light near the TiO2 particles will be bent and scattered to other places, making it difficult for the light to pass through the layer. Its working principle is as follows: Figure 1 shown.

[0031] The sunscreen is polymethylsilsesquioxane, with a particle size of 2 μm. The sunscreen is evenly dispersed in the matrix as fine spheres. Through the difference in refractive index with the substrate, the sunscreen changes the path of light, disperses the light source, reduces the light intensity, and softens the light.

[0032] The silica is precipitated silica with a refractive index of 1.4-1.6, a D50 of 8um-12um, and an oil absorption of 60%. A twin-screw extruder can be used to evenly disperse titanium dioxide in the silica, thereby filling gaps. During dispersion, titanium dioxide can form a complementary particle size with silica, thereby achieving a synergistic effect.

[0033] The mica powder D50 is 8-12 μm flake mica powder that can be dispersed within the sheet. Dispersion occurs when monoclinic mica crystals are inserted into the gaps between the adjacent silica and titanium dioxide. After extrusion and stretching, the resulting laminated structure is oriented and effectively blocks light. The stretched mica sheet forms a "wall"-like structure to block light. Furthermore, the mica powder's layered structure imparts birefringence, resulting in excellent light-blocking capabilities and further enhancing the light-blocking effect.

[0034] The antioxidant is a hindered phenol antioxidant or a phosphite antioxidant. To prevent the antioxidant itself from affecting the color, the antioxidant in the following embodiment is selected from oxidant B225. In addition to decomposing the peroxide (ROOH) generated after the antioxidant captures the peroxide free radical (ROO·), the main function of the antioxidant is to react with the peroxide to form a stable compound, prevent the peroxide from breaking down into free radicals, and effectively improve the aging resistance of the light-shielding container.

[0035] Specifically, in the following example, the carrier resin is Fushun Petrochemical homopolymer polypropylene T36, the titanium dioxide is DuPont's R-902, the silica is Wacker's hydrophobic series, the filler mica powder and the sunscreen are both commercially available, the dispersant is Kao's EBS, and the antioxidant is Suqian Liansheng B215 or B225, with B215 being specifically selected as the antioxidant.

[0036] Example 1-Example 5

[0037] The embodiments of the present application provide a method for preparing a composite light-shielding container. The specific components and proportions in each embodiment are shown in Table 1:

[0038] Table 1 Components and ratios of the composite light-shielding container in the preparation method of each embodiment

[0039] Example Carrier resin Silicon dioxide Titanium dioxide Mica powder sunscreen dispersants antioxidants 1 30 7 12 37 12 1.8 0.2 2 33 9 10 37 9 1.8 0.2 3 36 10.4 8 37 6.6 1.8 0.2 4 39 10.8 6 37 5.2 1.8 0.2 5 42 11.8 4 37 3.2 1.8 0.2

[0040] Meanwhile, the composite light-shielding container is prepared by the following steps:

[0041] S1. Accurately weigh the dispersant, antioxidant, and carrier resin in a mass ratio of 9:1:90 and premix them to prepare a premix with a dispersant and antioxidant percentage of 10%. Set the speed of the high-speed mixer to 50 r / min, mix and control the material temperature in the mixer to 65° C. for 15 minutes. After mixing, obtain premix A and mix it evenly.

[0042] S2. The six components of carrier resin, silica, titanium dioxide, sunscreen, mica powder, and premix A in Table 1 are placed in the silo above their corresponding loss-in-weight scales; the accuracy of A, B, C, D, E, and F is 0.02%, and the loss-in-weight scale is used for unloading and feeding;

[0043] S3. Set the proportion of each component according to the content in Table 1 on the operation panel of the loss-in-weight batching system;

[0044] S4. After the components are mixed by weight loss weighing, they are extruded through a twin-screw extruder (twin-screw 65 model) through a "T"-shaped die. The screw speed is set to 450 r / min, the extrusion pressure is 20 MPa, the temperature of each extrusion zone is set to 220°C, and the extrusion die temperature is controlled at 210°C; the obtained mixed melt is pelletized, dried, and cooled to produce a finished masterbatch.

[0045] S5. The finished masterbatch is drawn into sheets through multi-layer co-extrusion. The multi-layer co-extrusion is as follows:

[0046] Machine A (middle layer): carrier resin 20% + light-blocking masterbatch 80%, layer ratio 60%, screw speed 115r / min, extrusion temperature 200℃, extrusion pressure 12MPa;

[0047] Machine B (inner layer): carrier resin 94% + white masterbatch 6%, layer ratio 20%, screw speed 80r / min, extrusion temperature 210℃, extrusion pressure 8MPa;

[0048] Machine C (outer layer): carrier resin 94% + white masterbatch 6%, layer ratio 20%, screw speed 80r / min, extrusion temperature 190℃, extrusion pressure 8MPa;

[0049] S6. The sheet prepared in step S5 is calendered and cooled by a sheet drawing machine to a sheet width of 800 mm and a thickness of 3400 ± 50 μm. The temperatures of the three calendering rollers are respectively controlled at 32° C., 48° C., and 90° C., the temperature of the cold roller is controlled at 100° C., the sheet travel speed is 5 m / min, and the temperature of the sheet is controlled at 120° C. The prepared sheet is a white, opaque sheet with uniform thickness.

[0050] S7. The sheet prepared in step S6 is subsequently subjected to blister molding. The molding machine adopts radiation heating at a temperature of 360°C; a water-cooled mold is used, the temperature of the water-cooled mold is set to 25°C, the air pressure is 7 MPa, and the blister molding time is 5 seconds to obtain a composite light-shielding container.

[0051] The present application conducted a performance test on the composite light-shielding container prepared in Examples 1 to 5. The results showed that the composite light-shielding container in the present application had an effective volume of 250 ml and a white plastic cup. The thickness of the middle part of the cup body of the white plastic cup was 450 μm ± 50 μm. After being placed for 24 hours after molding, a sample at the middle of the cup body was taken for testing. The test performance included light transmittance, barrier properties, shelf life of dairy products, etc. The specific results are shown in Table 2:

[0052] Table 2 Performance test of the composite light-shielding containers prepared in Examples 1-5

[0053]

[0054]

[0055] From the contents of Table 2, it can be seen that Example 3 has a better effect. Adding silicon dioxide, titanium dioxide and mica powder to polypropylene helps to improve the light-blocking performance of the sheet. As the amount of silicon dioxide increases, the light-blocking property first increases and then decreases.

[0056] Comparative Example 1

[0057] The composite light-shielding container provided in this comparative example has components substantially the same as those in Example 3, except that the particle size of the titanium dioxide is 0.4 μm. The steps and process parameters of the preparation method are the same as those in Example 3.

[0058] Comparative Example 2

[0059] The composite light-shielding container provided in this comparative example has the same components as those in Example 3, except that the particle size of the light-shielding agent is 10 μm. The steps and process parameters of the preparation method are the same as those in Example 3.

[0060] Comparative Example 3

[0061] The composite light-shielding container provided in this comparative example has components substantially the same as those in Example 3, except that the particle size of the silicon dioxide is 20 μm. The steps and process parameters of the preparation method are the same as those in Example 3.

[0062] Comparative Example 4

[0063] The composite light-shielding container provided in this comparative example has components substantially the same as those in Example 3, except that the particle size of the mica powder is 20 μm. The steps and process parameters of the preparation method are the same as those in Example 3.

[0064] Comparative Example 5

[0065] The composite light-shielding container provided in this comparative example has the same components as those in Example 3, and the steps and process parameters of its preparation method are basically the same as those in Example 3, except that the composite light-shielding container with the above components and formula is extruded in one go to prepare a sheet;

[0066] The present application conducted performance tests on the composite light-shielding containers prepared in Comparative Examples 1-5, and the results are shown in Table 3:

[0067] Table 3 Performance test of the composite light-shielding containers prepared in Comparative Examples 1-5

[0068]

[0069]

[0070] As can be seen from Table 3, the composite light-shielding container in this application, titanium dioxide of specific particle size, sunscreen, silica and mica powder work synergistically, combined with a specific layered structure, so that the composite light-shielding container has excellent light-shielding performance and molding processing performance, greatly reducing the production cost of the composite light-shielding container.

[0071] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and description of the present invention.

Claims

1. A composite light-shielding container, characterized in that: The composite light-shielding container is prepared by a three-layer co-extrusion method, including an outer layer, a middle layer and an inner layer, and includes the following components by mass percentage: 31% to 42% of carrier resin, 3% to 8% of titanium dioxide, 8% to 12% of silicon dioxide, 30% to 40% of mica powder, 3% to 7% of sunscreen, 0.5% to 2% of dispersant, and 0.1% to 0.4% of antioxidant; The outer layer includes 90-95% carrier resin + 4-10% white masterbatch, and the layer ratio accounts for 20%; the middle layer includes 15-30% carrier resin + 65-85% light-blocking masterbatch, and the layer ratio accounts for 60%; the inner layer includes 90-95% carrier resin + 4-10% white masterbatch, and the layer ratio accounts for 20%.

2. The composite light-shielding container according to claim 1, characterized in that: The light-blocking masterbatch comprises silicon dioxide, mica powder, a dispersant, a light-shielding agent and an antioxidant.

3. The composite light-shielding container according to claim 1, characterized in that: The white masterbatch is one or more of titanium dioxide, calcium carbonate and polyethylene, and the sunscreen is polymethylsilsesquioxane with a particle size of 1-3 μm.

4. The composite light-shielding container according to claim 3, characterized in that: The titanium dioxide is rutile titanium dioxide, and the content of the titanium dioxide is ≥99%, the particle size is 0.15-0.25um, the tinting power is ≥100, and the oil absorption is 16≤%≤24.

5. The composite light-shielding container according to claim 4, characterized in that: The silicon dioxide is fumed silicon dioxide with a particle size of D50=8um-12um and an oil absorption of ≤75; the particle size of the mica powder is D50=8um-12um.

6. The composite light-shielding container according to claim 4, characterized in that: The dispersant is N,N'-ethylene bisstearamide; and the antioxidant is a hindered phenol antioxidant or a phosphite antioxidant.

7. A method for preparing a composite light-shielding container according to any one of claims 1 to 6, characterized in that: The steps include: 1) Masterbatch preparation: ingredients are prepared according to the formula requirements, mixed, melt-extruded, and the melt is pelletized, dried, and cooled to form a masterbatch. The temperature of the melt extrusion is controlled to be 10-40°C above the melting point of the carrier resin; 2) Preparation of composite light-shielding container: The masterbatch prepared in step 1) is drawn into a sheet by multi-layer co-extrusion, and then calendered and vacuum-formed to obtain a composite light-shielding container.

8. The method for preparing a composite light-shielding container according to claim 7, characterized in that: The process parameters of the melt extrusion in step 1) are a screw speed of 400-500 r / min, an extrusion pressure of 15-25 MPa, an extrusion temperature of 210-240° C., and an extrusion die temperature of 210-220° C.

9. The method for preparing a composite light-shielding container according to claim 7, wherein: The process parameters of the multi-layer co-extrusion in step 2) are: temperature 190-225° C., and metering pump pressure controlled at 7-12 MPa.

10. The method for preparing a composite light-shielding container according to claim 7, characterized in that: The process parameters of the blister molding are: the temperature of the blister molding machine is 340-400° C., the air pressure is 6-8 MPa, and the time is 4-5 seconds.